Human resources costing information systems - Καλογερόπουλος, Μιχαήλ (2023)
A vital procedure in a corporation is budget preparation. The budget supports the company's strategy for achieving its objectives, vision, and mission. A higher standard of accuracy for the guidance is required in order to maintain a balanced cash flow and enhance the management of equity and debt. Traditional and activity-based budgeting are two methods that can both be used to construct the budget. The budget created in the traditional manner is ideal for businesses with few employees in their cost centres. On the contrary, activity-based budgeting (ABB) is based on activity-based costing (ABC), which assigns a predetermined cost per unit to each activity. More recently, techniques that offer the option of allocating the cost of human resources using the Full-Time Equivalent-FTE method have been developed in the literature. The Full-Time Equivalent (FTE) per activity results from the actual human effort of each employee per activity. It represents the actual cost of staff in a particular service area.